PENGARUH GAYA KEPEMIMPINAN PATERNALISTIK TERHADAP KINERJA PEGAWAI DI BAGIAN OTONOMI DAERAH SEKRETARIAT KABUPATEN KUTAI TIMUR - Fl. Sudiran Akhmad Fadil Hidayat (ADMINISTRASI PUBLIK, 2017)
This study aims to know the influence of paternalistic leadership on the performanceof employees in the Regional Autonomy Division of the Regional Secretariat of East KutaiRegency, therefore the researcher formulates the hypothesis "Suspected paternalisticleadership has an effect on the performance of employees of the Regional AutonomyDivision of the Regional Secretariat of East Kutai Regency".The timing of the research is conducted in August 2016 until February 2017 for 6(six) months. The research method in this research is quantitative, the data obtained throughdirect observation to the field, and distributing questionnaires to the speakers with the numberof samples is 20 (twenty) respondents.Based on Product Moment correlation calculation known there is correlation betweenpaternalistic leadership to employee performance with number 0,716. This figure isinterpreted as a strong correlation between paternalistic leadership towards employeeperformance.While the hypothesis test yields empirical rxy numbers of 0.716 where the rxy tablefor N = 20 (with 95% confidence level) is 0.444, then rxy empirical> rxy table. Thus it can besaid that there is a positive influence between paternalistic leadership variable (X) onperformance variable (Y) employee in the Regional Autonomy Division of East KutaiRegency Secretariat.